Penguatan Civic Resilience Mahasiswa Melalui Pendidikan Kewarganegaraan Pasca Pandemi Covid-19 - Ahmad Muhamad Musain Nasoha; Kamelia Maimunah; Annajmul Muniiroh; Annuriyah Nabila (Majelis: Jurnal Hukum Indonesia, 2025)
This study aims to analyze the strengthening of students' civic resilience through Civic Education (PKn) after the COVID-19 pandemic using qualitative methods based on literature review. The COVID-19 pandemic has changed students' social interaction patterns and learning methods, which have an impact on their social engagement and resilience as citizens. This study collects and evaluates literature related to the challenges of Civic Education learning and strategies for strengthening civic resilience in the post-pandemic context. The results show that participatory learning approaches, digital literacy, strengthening social values, and community service activities are key elements in strengthening students' cognitive and social resilience. Learning that integrates digital technology provides opportunities for students to participate more actively in social and political discussions. On the other hand, community service activities based on civic values ​​help students develop a stronger sense of social responsibility. The implications of this research encourage the development of a Civic Education curriculum that is adaptive to current social and technological dynamics so that students become resilient and active citizens. This study also recommends that Civic Education be continuously updated with a more interactive and relevant approach to current needs, to enhance students' ability to participate constructively in the global community.